Analisis Setelah Implementasi Merger Pada Perusahaan Telekomunikasi di Indonesia: Studi Kasus : Pt Indosat Ooredoo Hutchison - Feni Haryani; Fitria Nasta’in; Ika Novitasari; Endang Kartini Panggiarti (Lembaga Pengembangan Kinerja Dosen, 2023)
This study investigates the post-merger implementation at PT Indosat Ooredoo Hutchison, following the business combination agreement between PT Indosat Tbk and PT Hutchison Tri Indonesia. The merger implementation has substantial implications for both entities. The research employs a literature review methodology, conducting a descriptive analysis of preceding journals. Findings indicate a mixture of positive and negative effects resulting from the merger at PT Indosat Ooredoo Hutchison. Furthermore, the companies encounter various challenges in executing the merger. Limitations in this study include constraints related to available literature and the sample size, underscoring the necessity for refinements in subsequent research endeavors to yield comprehensive conclusions.